Recent increase in Antarctic Peninsula ice core uranium concentrations. (September 2016) - Potocki, Mariusz; Mayewski, Paul A.; Kurbatov, Andrei V.; Simões, Jefferson C.; Dixon, Daniel A.; Goodwin, Ian; Carleton, Andrew M.; Handley, Michael J.; Jaña, Ricardo; Korotkikh, Elena V.
Abstract: Understanding the distribution of airborne uranium is important because it can result in both chemical and radiological toxicity. Ice cores offer the most robust reconstruction of past atmospheric levels of toxic substances. Here we present the first sub-annually dated, continuously sampled ice core documenting change in U levels in the Southern Hemisphere. The ice core was recovered from the Detroit Plateau, northern Antarctic Peninsula, in 2007 by a joint Brazilian-Chilean-US team. It displays a significant increase in U concentration that coincides with reported mining activities in the Southern Hemisphere, notably Australia. Raw U concentrations in the Detroit Plateau ice core increased by as much as 10 2 between the 1980s and 2000s accompanied by increased variability in recent years. Decadal mean U concentrations increased by a factor of ∼3 from 1980 to 2007, reaching a mean of 205 pg/L from 2000 to 2007. The fact that other terrestrial source dust elements such as Ce, La, Pr, and Ti do not show a similar increase and that the increased U concentrations are enriched above natural crustal levels, supports an anthropogenic source for the U as opposed to a change in atmospheric circulation. Highlights: First highly detailed, continuous U record from an Antarctic ice core. U concentrations increase up to 10 2 between the 1980s and 2000s. Since the 1990s, raw U, excess U, and U EFc values have increased significantly. Rise in U primarily attributed to Southern Hemisphere anthropogenic emissions.